2018
DOI: 10.1093/mnras/sty535
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the non-Gaussianity in the EoR 21-cm signal through bispectrum

Abstract: The epoch of reionization (EoR) 21-cm signal is expected to be highly non-Gaussian in nature and this non-Gaussianity is also expected to evolve with the progressing state of reionization. Therefore the signal will be correlated between different Fourier modes (k). The power spectrum will not be able capture this correlation in the signal. We use a higherorder estimator -the bispectrum -to quantify this evolving non-Gaussianity. We study the bispectrum using an ensemble of simulated 21-cm signal and with a lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 106 publications
10
149
0
1
Order By: Relevance
“…There is no fourth-moment (kurtosis) present. (More recent analysis by Majumdar et al 2018, shows similar results.) To study the observed visibility distributions, we can perform moments analysis directly on the KDE outputs 1 .…”
Section: Moments Analysissupporting
confidence: 64%
“…There is no fourth-moment (kurtosis) present. (More recent analysis by Majumdar et al 2018, shows similar results.) To study the observed visibility distributions, we can perform moments analysis directly on the KDE outputs 1 .…”
Section: Moments Analysissupporting
confidence: 64%
“…When applied to the 21-cm signal, eq. (2.9) has the key virtue that it contains more information than the power spectrum, but is simpler to estimate compared to the conventional bispectrum estimators [11,14,15].…”
Section: Position-dependent Power Spectrum As a Probe Of The Squeezedmentioning
confidence: 99%
“…Note that the oscillations on the left side of the peak are due to the sharp edges of the bubbles: when symmetrical Gaussian distributions are used instead of binary bubbles, or once the field is smoothed by a given angular resolution, they vanish. We refer the interested reader to Watkinson et al (2017) and Majumdar et al (2018), where the authors discuss the various problems induced by solid spheres in the bispectrum. Finally, a comparison of numerical results with an analytical derivation of the TCF for a similar toy model can eb found in Appendix A.…”
Section: Application To Simulated Ionisation Fieldsmentioning
confidence: 99%